ANALYSIS OF THE EFFECTS AND ADVANTAGES OF E-SPT AND E-FILING IMPLEMENTATION ON TAXPAYER KNOWLEDGE AND COMPLIANCE - Mekar Meilisa Amalia; Fatimah Fatimah; Renika Hasibuan; Hasmidar Hasmidar; Ismet Ismatullah (Jurnal Ekonomi, 2023)
As the primary source of state revenue, taxes finance infrastructure and public services. The Indonesian government implements information technology innovations such as E-SPT and E-Filing in the taxation system. Modernizing taxation with an electronic system is anticipated to improve tax collection and taxpayer conformance. Prior research demonstrates the significance of taxpayer awareness and compliance with this system. This study seeks to assess taxpayers' use of and compliance with e-SPT and e-Filing. Frequently occurring issues with tax payments can impede the tax collection process. This research is essential for enhancing the efficacy of the tax administration system and taxpayer compliance. The results demonstrate that e-SPT and e-filing have a significant impact on taxpayer compliance, both individually and concurrently.